Therapeutic exercise interventions in pediatric survivors of brain cancer and other solid tumors: A scoping review - Kohler, Brooke E.; Sandler, Carolina X.; Baque, Emmah; Bradford, Natalie K.; Trost, Stewart G. (Frontiers in Pediatrics, 2022)
Background: Improved survival rates for children with solid tumors presents an ongoing challenge of how to maximize quality of survivorship and effectively manage the short- and long-term complications of disease and treatment. To gain an understanding of the extent and nature of research pertaining to therapeutic exercise interventions and identify knowledge gaps, we conducted a scoping review of exercise training studies conducted in pediatric survivors of brain cancer and other solid tumors. Method: A systematic literature search was performed across four electronic databases. Papers were selected for full-text review if they included participants treated for brain cancer or other solid tumors, with at least 50% of participants aged ≤21 years, evaluated an exercise intervention ≥2-weeks in duration, and were published in an English, peer-reviewed journal. We included the following quantitative study designs; randomized controlled trials, non-randomized trials, and single-arm pre-test-post-test. Results: Of the 7,482 citations identified, 17 papers met the inclusion criteria (presenting findings from eleven studies). Two studies were randomized controlled trials, five studies were non-randomized controlled trials, and four studies were a single-arm pre-test post-test design. Average age of participants ranged from 7.3-15.5 years, and time since diagnosis ranged from three to 70 months. Five studies included participants with brain tumors exclusively, three studies included other solid tumors, and three studies included a mixed sample (brain and other solid tumours). A wide range of exercise modalities were employed, including cycle ergometry, resistance training, sport, yoga, and active gaming. The length of the exercise program ranged from 3-40 weeks and frequency from 3-11 sessions per week. Exercise session duration ranged from 15-180 minutes, with most studies reporting 30–90-minute sessions. Adherence ranged from 77% to 100%, with none of the studies reporting adverse events. Studies reported improvements in cardiorespiratory fitness, functional strength, physical activity, and quality of life. Conclusions: A small number of mostly low methodological quality studies have examined the effects of therapeutic exercise in pediatric survivors of solid tumors. Although limited, the extant literature supports the feasibility and safety of therapeutic exercise interventions for pediatric survivors of brain cancer and other solid tumors.